Exploring the vertical accretion of ornithogenic sediments from the Xisha Islands, South China Sea, by seabird subfossils. (22nd August 2018) - Xu, Liqiang; Zhao, Jinjun; Wu, Libin; Chen, Lin; Liu, Xiaodong
ABSTRACT: Reef islands of the Xisha Islands, South China Sea, were formed during the mid–late Holocene. However, the vertical accretion of ornithogenic sediments of the islands is not well understood owing to a lack of precise dating. Here we present an analysis of seven of the Xisha Islands, and reconstruct their accumulation history based on radiocarbon analysis of seabird subfossils. From Clam‐based age–depth models, a universal development mode of the Xisha Islands is hypothesized. The mean accumulation rate of guano sediments on the Xisha Islands in the late Holocene was 1.02 ± 0.42 mm a −1 . The sum of the deposition rate of coral sands and the rate of ornithogenic accumulation is lower than or close to the current rate of sea level rise in the Xisha Islands, implying a potential threat to the islands' safety. This study also provides robust evidence for a sequence of island development associated with seabirds.